2016
DOI: 10.18632/oncotarget.8571
|View full text |Cite
|
Sign up to set email alerts
|

Protein profiling of alpha-fetoprotein producing gastric adenocarcinoma

Abstract: Alpha-fetoprotein (AFP) producing gastric adenocarcinoma is considered as a rare subtype of gastric adenocarcinoma. Compared with AFP non-producing gastric adenocarcinoma, our study and other previous studies showed that AFP producing gastric adenocarcinoma is more aggressive and prone to liver metastasis. Using the Protein Pathway Array, 11 of out of 286 proteins tested were found to be differentially expressed between AFP producing (n=32) and AFP non-producing (n=45) gastric adenocarcinoma tissues. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Moreover, elevated serum levels of AFP indicates the growth of malignant lung and bladder tumors as well as gastrointestinal cancers of stomach, pancreas, and colon (Mizejewski, 2014). High mortality and morbidity rates were reported to patients with AFP-positive-gastrointestinal cancer (AFP(+)GC) than AFP(-)GC-patients due to active cell proliferation, high mitotic rate, amplified cell invasion and migration, rapid tumor progression and advanced tumor stage (He et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated serum levels of AFP indicates the growth of malignant lung and bladder tumors as well as gastrointestinal cancers of stomach, pancreas, and colon (Mizejewski, 2014). High mortality and morbidity rates were reported to patients with AFP-positive-gastrointestinal cancer (AFP(+)GC) than AFP(-)GC-patients due to active cell proliferation, high mitotic rate, amplified cell invasion and migration, rapid tumor progression and advanced tumor stage (He et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-122-5p was not correlated with liver metastasis of non-AFPGC in clinical settings (data not shown). He et al (30) revealed that upregulated Bcl-2 (anti-apoptotic protein) was correlated with liver metastasis of AFPGC in clinical settings. Similarly, the protein level of Bcl-2 was decreased by inhibition of miR-122-5p in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…He et al, [38] using the protein pathway array, 11 of out of 286 proteins tested were found to be differentially expressed, and several of them correlated with prognosis of AFP producing gastric adenocarcinoma. Two of them were worth mentioning; XIAP (X-linked inhibitor of apoptosis) and IGFIrβ (Insulin-like growth factor-I receptor β).…”
Section: Molecular Biology Of Afp-gcmentioning
confidence: 99%
“…The 1-,3-,5-year survival rates for AFP>300ng/ml were 15.4%, 7.7%, and 0% respectively. In three studies [21,23,38,57], multivariate survival analysis revealed that AFP positivity to be the independent prognostic factor. In the study by Liang et.al.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation